Silver nanoparticles in aquatic environments: Physiochemical behavior and antimicrobial mechanisms. (1st January 2016) - Zhang, Chiqian; Hu, Zhiqiang; Deng, Baolin
Abstract: Nanosilver (silver nanoparticles or AgNPs) has unique physiochemical properties and strong antimicrobial activities. This paper provides a comprehensive review of the physicochemical behavior (e.g., dissolution and aggregation) and antimicrobial mechanisms of nanosilver in aquatic environments. The inconsistency in calculating the Gibbs free energy of formation of nanosilver [ ΔG f ( AgNPs ) ] in aquatic environments highlights the research needed to carefully determine the thermodynamic stability of nanosilver. The dissolutive release of silver ion (Ag + ) in the literature is often described using a pseudo-first-order kinetics, but the fit is generally poor. This paper proposes a two-stage model that could better predict silver ion release kinetics. The theoretical analysis suggests that nanosilver dissolution could occur under anoxic conditions and that nanosilver may be sulfidized to form silver sulfide (Ag2 S) under strict anaerobic conditions, but more investigation with carefully-designed experiments is required to confirm the analysis. Although silver ion release is likely the main antimicrobial mechanism of nanosilver, the contributions of (ion-free) AgNPs and reactive oxygen species (ROS) generation to the overall toxicity of nanosilver must not be neglected. Several research directions are proposed to better understand the dissolution kinetics of nanosilver and its antimicrobial mechanisms under various aquatic environmental conditions. Graphical abstract: Highlights: Gibbs free energy of formation of nanosilver in aquatic environments was analyzed. The dissolution model of nanosilver is critically evaluated and improved. Nanosilver aggregation depending on its thermodynamics can be quantified. Antimicrobial activities of nanosilver are mainly governed by its dissolution. The behavior of nanosilver and its interactions with microbes need more research.